Da concepção à negação da fraude corporativa: uma análise processual do caso do Banco BVA/KPMG - Carvalho, Helton Pena de (2016)
One of the practices of the dark side analyzed in the field of Organizational Studies refers to Corporate Crimes, specially the kind “Corporate Frauds”. Even though many efforts have been made to avoid these frauds they still happen frequently, for example in cases involving Boi Gordo, Banco Santos and Daslu. In the cases Boi Gordo and Banco Santos, Costa (2011) identified the characteristic elements of the fraud itself and how a favorable environment for it to happen was created. Studies such as the one performed by Costa (2011) are still relatively new in literature specially the ones that deal with antecedents of Corporate Frauds. This research has as its main goal to analyze the Corporate Fraud that happened in Banco BVA, and which had the participation of KPMG Auditores Independentes, as a process, mainly the conduct of KPMG while responsible for the auditing of Banco BVA. We are trying, therefore, to recognize the individual and organizational dimensions which preceded the occurrence of the fraud at that financial institution, understand how KPMG acted to help the fraud at Banco BVA to happen as well as analyze the defense arguments of KPMG concerning their responsibility in the Banco BVA fraud. The research had as its groundwork the previous studies about the antecedents of corporate crimes such as Bashir et al. (2011), Baucus (1994) e Zahra, Priem e Rasheed (2005) as well as the Costa (2011) thesis, specially according to the categories related to the antecedents of Corporate Frauds. The study was achieved by documental analyses using the active lawsuits at the Tribunal de Justiça do Estado de São Paulo which has KPMG as procedural part. From all ten categories chosen to identify the antecedents of Corporate Fraud, only tree were not identified in the analyzed case: Lack of Reporting, Corporate Culture (BASHIR et al.; 2011) and Organization (ZAHRA; PRIEM; RASHEED, 2005) as far as the corporate governance of Banco BVA is concerned. The study contributes to the understanding of the Corporate Fraud since it highlights the subjects and, most of all, because it is such a recent event. The research extended the understanding of fraud as a process, having contributed to the knowledge in the area of the Organizational Studies, chiefly emphasizing events that occur in the dark side of Organizations i.e. events that are rarely studied and which, however, are part of Corporate operations. The research shows the necessity to observe the relationship between Auditing Firms and audited subjects. These aspects must be taken into consideration, as to the choice of the Auditing Firm, in relation to members of the internal team who will deal with the Auditing Firm, as well as being aware of risks concerning the hiring of former employees of the Auditing Firms who are, or might eventually become, clients of these firms.